Environmental Accounting and Financial Management: A Strategic Approach to Corporate Sustainability - Huliselan, Meny (SAFE-Network, 2025)
This paper explores the strategic convergence of environmental accounting and financial management in advancing corporate sustainability. As organizations face growing regulatory, investor, and societal demands, the integration of environmental performance metrics into financial decision-making has become essential for long-term value creation. The review synthesizes recent scholarly work (2019–2024) across thematic areas such as environmental accounting tools, sustainable financial planning, institutional drivers, integration challenges, and technological innovations. Findings suggest that while firms increasingly embed sustainability considerations into capital budgeting, risk assessment, and reporting practices, barriers such as data inconsistency, lack of standardization, and organizational silos persist. The paper identifies critical research gaps and highlights the need for empirical, cross-sectoral studies, harmonized disclosure frameworks, and digital solutions to support this integration. Ultimately, the convergence of environmental and financial disciplines presents a transformative opportunity to align economic goals with environmental responsibility.